Are Irish voters biased against female candidates? Evidence from the 2020 general election - Keenan, Lisa (My University, 2021)
Ireland is the first country in the world to apply a legislative gender quota under an STV electoral system. Since 2016, the quota has required parties to ensure that at least thirty percent of their candidates running in the general election are women. Due to the nature of the electoral system, namely that it is candidate-centred, the impact of the quota has the potential to be limited if voter bias is present among the electorate. While the initial gains from the quota’s first election in 2016 were maintained at the 2020 general election, with one more woman elected to Dáil Éireann, the headline figures may be misleading. In this earthquake election, a significant number of high-profile women from across the political spectrum lost their seats, while male colleagues retained theirs, suggesting that female candidates may have been evaluated differently from their male counterparts. Using self-reported voter attitudes from the 2020 Irish National Election Study, we investigate whether there is an underlying bias against women amongst voters. We test whether such a bias has an impact on the share of women running and the share of women winning, as well as individual women’s level of electoral success. Overall, we find no evidence that voter bias affected outcomes for women at the 2020 Irish general election.
PUBLISHED
https://doi.org/10.1080/07907184.2021.1980651
Keywords: Gender; Voter bias; Voter behaviour; Candidate selection; Inclusive Society; Irish Political Parties; Irish politics; Irish politics, election study, electoral behaviour; Political Participation; Political parties; Politics and Gender; Gender